2020
DOI: 10.1002/chem.202000212
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Biophysical Techniques Reveal Structural Mechanisms of Engineered Cationic Antimicrobial Peptides in Lipid Model Membranes

Abstract: In the questf or new antibiotics, two novel engineered cationic antimicrobialpeptides (eCAPs)h ave been rationallyd esigned. WLBU2 and D8 (all 8v alines are the denantiomer)e fficiently kill both Gram-negative and -positive bacteria, but WLBU2 is toxic and D8 nontoxict oe ukaryotic cells. We explore protein secondary structure, location of peptides in six lipid model membranes, changes in membrane structurea nd pore evidence. We suggest that protein secondary structure is not ac riticald eterminant of bacteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 62 publications
3
36
0
Order By: Relevance
“…Several studies have examined how PLG0206 exhibits bactericidal efficacy. Heinrich et al [ 21 ] showed that neither the secondary structure nor pore formation is a critical determinant of bactericidal efficacy for PLG0206. The interaction of PLG0206 with the bacterial cell membrane leads to lipid phase consolidation, resulting in localized stiffening [ 22 ], ordering, and alteration of the thickness of the membranes [ 21 ].…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined how PLG0206 exhibits bactericidal efficacy. Heinrich et al [ 21 ] showed that neither the secondary structure nor pore formation is a critical determinant of bactericidal efficacy for PLG0206. The interaction of PLG0206 with the bacterial cell membrane leads to lipid phase consolidation, resulting in localized stiffening [ 22 ], ordering, and alteration of the thickness of the membranes [ 21 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…Heinrich et al [ 21 ] showed that neither the secondary structure nor pore formation is a critical determinant of bactericidal efficacy for PLG0206. The interaction of PLG0206 with the bacterial cell membrane leads to lipid phase consolidation, resulting in localized stiffening [ 22 ], ordering, and alteration of the thickness of the membranes [ 21 ]. Consequently, this disruption of the bacterial cell membrane results in lipid headgroup spacing mismatch and lowering of the energy barrier to ion flow across the membrane.…”
Section: Pharmacologymentioning
confidence: 99%
“…Colistin, or polymyxin E, is a cationic lipopeptide and “last-resort” antibiotic used for MDR Gram-negative infections, such as those producing extended-spectrum beta-lactamases and those resistant to carbapenems ( 6 ), which is an increasing concern in clinical isolates of Enterobacter species ( 7 ). Targeting the cell membrane, cationic colistin binds with anionic lipopolysaccharide (LPS) through electrostatic interactions ( 8 11 ). Colistin resistance is conferred by reduction of the electronegativity of the cell membrane through modification of the terminal phosphate residues of lipid A, the membrane anchor of LPS, thereby decreasing the binding affinity of colistin ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 The detailed secondary structure of WLBU2 in four different lipid model membranes (LMMs) and in aqueous solution was obtained using circular dichroism spectroscopy and was published previously. 16 While WLBU2 in water or 15 mM phosphate-buffered saline (PBS) adopts primarily a random coil or β-sheet structure, the α helical content increases to ∼80% in Gram-negative (G(−)) inner membrane (IM) or Gram-positive (G(+)) LMMs and to ∼40% in lipopolysaccharide (LPS)containing LMMs. Although WLBU2 is not 100% helical by our determination, 16 it is still primarily helical when in contact with the inner membrane of G(−) and G(+) LMMs, partially confirming the locations of R and V on opposite faces in WLBU2′s helical wheel rational design.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 While WLBU2 in water or 15 mM phosphate-buffered saline (PBS) adopts primarily a random coil or β-sheet structure, the α helical content increases to ∼80% in Gram-negative (G(−)) inner membrane (IM) or Gram-positive (G(+)) LMMs and to ∼40% in lipopolysaccharide (LPS)containing LMMs. Although WLBU2 is not 100% helical by our determination, 16 it is still primarily helical when in contact with the inner membrane of G(−) and G(+) LMMs, partially confirming the locations of R and V on opposite faces in WLBU2′s helical wheel rational design. When added to a eukaryotic membrane mimic, we found only a low level of αhelicity (∼20%).…”
Section: ■ Introductionmentioning
confidence: 99%